2008
DOI: 10.1074/jbc.m801402200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phosphatases Mediate the Deactivation of the DNA Damage Checkpoint Kinase Rad53

Abstract: The DNA damage checkpoint regulates DNA replication and arrests cell cycle progression in response to genotoxic stress. In Saccharomyces cerevisiae, the protein kinase Rad53 plays a central role in preventing genomic instability and maintaining viability in the presence of replication stress and DNA damage. Activation of Rad53 depends on phosphorylation by the upstream kinase Mec1, followed by autophosphorylation on multiple residues. Also critical for cell viability, the molecular mechanism of Rad53 deactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
66
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 52 publications
2
66
0
2
Order By: Relevance
“…The protein phosphatases Pph3, Ptc2, and Ptc3 appear to be dispensable for Rad53 deactivation following HU-induced S phase arrest, while they allow Rad53 deactivation and replication fork restart after MMS exposure (26,32,35). Although Rad53 dephosphorylation is delayed in HU-treated glc7 mutants, it still takes place, raising the possibility that Pph3, Ptc2, and/or Ptc3 might be engaged in cells crippled for Glc7 activity.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…The protein phosphatases Pph3, Ptc2, and Ptc3 appear to be dispensable for Rad53 deactivation following HU-induced S phase arrest, while they allow Rad53 deactivation and replication fork restart after MMS exposure (26,32,35). Although Rad53 dephosphorylation is delayed in HU-treated glc7 mutants, it still takes place, raising the possibility that Pph3, Ptc2, and/or Ptc3 might be engaged in cells crippled for Glc7 activity.…”
Section: Resultsmentioning
confidence: 78%
“…30,2010 Glc7 AND CHECKPOINT INACTIVATION 141 on May 9, 2018 by guest http://mcb.asm.org/ ery after HU-induced fork stalling. According to previous studies (35), we found that pph3⌬ and ptc2⌬ ptc3⌬ cells, which displayed a slight sensitivity to MMS that was enhanced in the triple mutant pph3⌬ ptc2⌬ ptc3⌬, were not more sensitive to HU than wild-type cells (Fig. 8A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result demonstrates that proper control of the amplitude and inactivation of the S-phase checkpoint is also essential for DNA replication control in the presence of replication stress. It also has been shown that other modes of checkpoint deactivation exist that have yet to be identified, highlighting the need for more studies on checkpoint deactivation mechanisms (Travesa et al 2008).…”
mentioning
confidence: 99%